Diseminasi Sistem Jaminan Produk Halal Berbasis Komunitas: Studi pada Persati Beken di Medan - Yogi Putra; Tina Linda; Devia Febrina; Lidia Berliana Siboro; Mega Hernawati Harefa (Pusat Riset dan Inovasi Nasional, 2025)
The socialisation of information about the Halal Product Guarantee System aims to open the insights and knowledge of MSME players regarding the benefits and importance of halal certification on products. The method used by the service team is through structured socialisation activities regarding the system. The results of this activity show that the entire series of socialisation went smoothly, and received a positive response from MSME players. They feel motivated and encouraged to immediately take part in further activities, including halal companion training which is one of the main requirements in the process of applying for product halal certification